UK macroalgae aquaculture: What are the key environmental and licensing considerations?. (September 2017) - Wood, Daniel; Capuzzo, Elisa; Kirby, Damien; Mooney-McAuley, Karen; Kerrison, Philip
Abstract: Macroalgae has numerous commercial uses and the potential to create large carbon sinks. The study reviewed the legal context, including environmental and social aspects, for the setting up of a seaweed farm in the UK. A lease is required to use the seabed and a Marine Licence is required from the national regulator. There is no need for new legislation, however, the existing guidance should be updated. There is a major need to clarify what level of assessment is required as part of the marine licensing process. The environmental and social considerations to licensing were also reviewed. Changes to the hydrodynamics and sediment transport are expected in and around the farm. These may lead to changes in seabed siltation and light levels. The addition of hard substrate (from the anchors) and a macroalgae canopy lead to attraction of benthic animals, fish, marine mammals and birds. These, in addition to potential changes in organic matter and nutrients reaching the seabed from exudate and detritus, could create changes in existing benthic communities on the seafloor. No reason for major population-level impacts were seen. However, numerous knowledge gaps where identified. Scale appears to be an important consideration. A small farm on its own is unlikely to have a large effect on the marine environment. However, a very large farm, or multiple small farms next to each other could have a more notable effect. Knowledge gaps were identified and recommendations were provided that can assist the development of the UK macroalgae farming industry. Highlights: Legal and regulatory context of setting up a macroalgae farm were reviewed. The potential for environmental effects from a macroalgae farm were considered. No impacts were identified but multiple knowledge gaps were found. Recommendations that will both assist the macroalgae farming industry and regulators were provided.